Mandatory Minimum Policy Reform and the Sentencing of Crack Cocaine Defendants: An Analysis of the Fair Sentencing Act - David J. Bjerk (Institute for the Study of Labor (IZA), 2016)
The Fair Sentencing Act of 2010 (FSA) affected the U.S. federal mandatory minimum sentencing laws for to crack cocaine offenders, and represented the first Congressional reform of sentencing laws in over 20 years. A primary goal of this legislation was to lessen the harshness of sentences for crack cocaine offenders and decrease the sentencing gap between crack defendants and powder cocaine defendants. While both the mean sentence length for crack offenders fell following the implementation of the FSA, these changes appear to primarily reflect the continuation of on-going sentencing trends that were initiated by a variety of non- Congressional reforms to federal sentencing policy that commenced around 2007. However, the FSA appears to have been helpful in allowing these trends to continue past 2010.
Keywords: K40; 330; mandatory minimums; fair sentencing act; crack cocaine; powder cocaine; sentencing guidelines